DANCING INTO THE DIGITAL AGE: PRESERVING INDIAN CLASSICAL DANCE NARRATIVES THROUGH VIRTUAL AVATARS - Dawn, Suma; Bhattacharya, Monali (ShodhKosh: Journal of Visual and Performing Arts, 2025)
In this work, we explored methods for expressing dance narratives in a sequence on a virtual avatar, particularly in the context of Indian classical dance styles. This study has many different goals. First of all, it would aid in the preservation of multiple dance practices that are rapidly disintegrating since there aren't enough learners to impart lessons to them. Second, it may inspire a younger audience to be more engaged in discovering more about their cultural heritage by recasting it into a format that is easily accessible to them and can be valuable. Furthermore, this research will facilitate the organization of dance subtleties' morphology as well as their translation, retrieval, and storage processes. The aforementioned requirements, which are ontological and resource-intensive, would aid in digitizing vintage dance forms, making it easier to navigate information heading onward, including comprehending meaning, translating it into other languages, using rhythm, and other labour-intensive operations. This paper includes an examination of several approaches and strategies that are currently in use and could potentially implemented in future endeavours for the translation, conservation, and preservation of dance narratives. This research investigates the process of transforming dancer-choreographed stories into inanimate objects and virtual characters. It aims to explore animation techniques for converting Indian dance forms into animated narration, preserving cultural heritage, understanding emotions in animated sequences, and mapping body movements to capture dance structures' essence.